Study on Quasi-linear Stochastic Programming Model and Its Solution - Ji Xiangjun; Jin Chenxia (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In this paper, we first analyze the features and shortcomings of existing stochastic programming methods. For the bottleneck of higher computational complexity, we give the concept of reliability coefficient and a quasi-linear processing pattern for chance-constrain based on mathematic expectation and variance, analyze the relationship between reliability coefficient and reliability (probability), and give the selecting strategy of reliability coefficient. Then, we establish the quasi-linear stochastic programming model, and discuss the performance of this model by an example.